2021
DOI: 10.1021/acschembio.1c00604
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Assessment of Accessibility to the Surface of Staphylococcus aureus

Abstract: Proteins from bacterial foes, antimicrobial peptides, and host immune proteins must navigate past a dense layer of bacterial surface biomacromolecules to reach the peptidoglycan (PG) layer of Gram-positive bacteria. A subclass of molecules (e.g., antibiotics with intracellular targets) also must permeate through the PG (in a molecular sieving manner) to reach the cytoplasmic membrane. Despite the biological and therapeutic importance of surface accessibility, systematic analyses in live bacterial cells have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 71 publications
(102 reference statements)
0
26
0
Order By: Relevance
“…Regarding Gram-positive bacteria, peptidoglycan and LTA have been reported to act as either peptide ‘sponges’, increasing their local concentration, or as peptide ‘traps’, keeping them away from the lipid membrane (Malanovic and Lohner, 2016a). A recent study strongly suggested that WTA and LTA strongly impeded the access of variable molecules to the surface of S. aureus membrane (Ferraro et al ., 2021).…”
Section: Trp-containing Amps and Glycoconjugatesmentioning
confidence: 99%
“…Regarding Gram-positive bacteria, peptidoglycan and LTA have been reported to act as either peptide ‘sponges’, increasing their local concentration, or as peptide ‘traps’, keeping them away from the lipid membrane (Malanovic and Lohner, 2016a). A recent study strongly suggested that WTA and LTA strongly impeded the access of variable molecules to the surface of S. aureus membrane (Ferraro et al ., 2021).…”
Section: Trp-containing Amps and Glycoconjugatesmentioning
confidence: 99%
“…From these data, we were able to further demonstrate the binding propensity of P1fl to The accessibility of immune proteins to its bacterial cell wall target is largely mitigated by the presence of large surface polymers, wall teichoic acid (WTA) and lipoteichoic acid (LTA). Our lab, 76 and others, [77][78][79][80] have recently demonstrated that WTA play a major contribution to the accessibility of molecules to the PG of bacterial cells;…”
Section: Resultsmentioning
confidence: 84%
“…The accessibility of immune proteins to its bacterial cell wall target is largely mitigated by the presence of large surface polymers, wall teichoic acid (WTA) and lipoteichoic acid (LTA). Our lab, 76 and others, [77][78][79][80] have recently demonstrated that WTA play a major contribution to the accessibility of molecules to the PG of bacterial cells; therefore, we aimed to investigate the role that WTA plays on the accessibility of P1fl to the surface of E. faecalis, as WTA is the most highly abundant glycopolymer on the enterococci cell wall. 81,82 To achieve this, sacculi isolated from E. faecalis were treated with acid to hydrolyze the phosphodiester linkage between WTA and the PG, effectively removing the WTA from the isolated PG.…”
Section: Resultsmentioning
confidence: 99%
“…The basis of the screening assay is site-specific incorporation of a biorthogonal handle via metabolic remodeling of bacterial PG. 11 More specifically, an unnatural amino acid (D-LysAz) is supplemented in the media, inoculated with S. aureus, and cultured overnight (Figure 2A). During PG biosynthesis and assembly, transpeptidases catalyze the replacement of the fifth position D-alanine on the stem peptide within the bacterial PG scaffold for D-LysAz, thus leading to the covalent installation of the azido-handle (Figure 2B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…9,10 It was proposed that BPEI neutralization of negatively charged polymers on the bacterial cell surface improved permeability. 11 These examples demonstrate that improved permeation to the essential cell wall components can be a powerful modality of reducing intrinsic resistance to small molecule antibacterials and immune proteins. 12 The cell walls of bacteria are complex in structure and composition.…”
mentioning
confidence: 99%